The effect of cognitive- behavioral training on depression and psychological hardiness of Patient With cardiovascular diseases - Mostafa Peyambari; Maryam Sadeghi; Mehran Rashidi; Mohsen Ahmadi tahour (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Depression is one of the risk factors for cardiovascular disease leading to re-admission, reduced quality of life, and increased risk of mortality. On the other hand, some people often tolerate and adapt to life problems and pressures more than others. Therefore, the purpose of the present study was to use cognitive-behavioral therapy to reduce depression and increase psychological hardiness in order to reduce the problems of patients with cardiovascular disease. Materials and Methods: In this study, a semi-experimental design with pre-test, post-test and control group was performed. The study population included all patients with heart disease men and women over twenty years and was down sixty years that were hospitalized in Farshchian hospital in Hamedan. Of this numbers, thirty people were selected by convenience sampling method and randomly divided into two groups of 15 participants and control. In order to evaluate depression from Beck Depression Inventory and measure the hardiness of personal opinion survey test were used. Then, using 10 sessions of cognitive behavioral therapy, changes in the post test were measured. Research data using multivariate analysis of covariance were analyzed. Results: The findings showed that teaching cognitive-behavioral therapy, reducing the rate of depression among heart patients. Also, this treatment increases the psychological hardiness. Conclusion: The findings of the present study cognition and conceptualization of the variables presented, it is possible to use cognitive-behavioral therapy in reducing depression and increasing hardiness benefit heart patients.